PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN LAPANGAN - Ega Syafiqi; Parwoto Parwoto (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
This study aims to analyze the effect of work discipline and work motivation on the performance of field employees at PT Jasuma Putri Putra. The population in this study were 40 field employees at PT. Jasuma Putri Putra. The sample used was the entire population of 40 employees. The sampling method uses Saturated Sampling. Data collection methods using survey methods, the research instrument is a questionnaire. Data analysis method uses Statistical Product and Service Solutions. This study proves that the effect of work discipline has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Keywords: Work Dicipline, Work Motivation, Employee Performance, Employees